Mitochondrial Fission and Fusion in Tumor Progression to Metastasis - Boulton, Dillon P.; Caino, M. Cecilia (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria are highly dynamic organelles which can change their shape, via processes termed fission and fusion, in order to adapt to different environmental and developmental contexts. Due to the importance of these processes in maintaining a physiologically healthy pool of mitochondria, aberrant cycles of fission/fusion are often seen in pathological contexts. In this review we will discuss how dysregulated fission and fusion promote tumor progression. We focus on 1) molecular mechanisms involved in fission and fusion, 2) how altered mitochondrial fission and fusion change tumor cell growth, metabolism, motility, and invasion and 3) how changes to these cell intrinsic phenotypes directly and indirectly impact tumor progression to metastasis. Although this is an emerging field of investigation, the current consensus is that mitochondrial fission positively influences metastatic potential in a broad variety of tumor types. As mitochondria are now being investigated as vulnerable targets in a variety of cancer types, we underscore the importance of their dynamic nature in potentiating tumor progression.